In search of the Hebrew people : Bible and nation in the German Enlightenment - Ilani, ʿOfri (German Jewish cultures, 2018)
"As German scholars, poets, and theologians searched for the origins of the ancient Israelites, Ofri Ilany believes they created a model for nationalism that drew legitimacy from the Biblical idea of the Chosen People. In this broad exploration of eighteenth-century Hebraism, Ilany tells the story of the surprising role that this model played in discussions of ethnicity, literature, culture, and nationhood among the German-speaking intellectual elite. He reveals the novel portrait they sketched of ancient Israel and how they tried to imitate the Hebrews while forging their own national consciousness. This sophisticated and lucid argument sheds new light on the myths, concepts, and political tools that formed the basis of modern German culture"...